Productive and qualitative performance of tomato plants as a function of the application of plant growth regulators and mineral nutrients - Caixeta Sousa, Marília; Sobreira Rodrigues, Luan Fernando Ormond; Bartira Da Silva, Mônica; Cruz, Janaina Oliveira; Diamante, Marla Silvia; Martins, Bruno Novaes Menezes; Simonetti, Lilian Massaro; Rodrigues, João Domingos (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 416-424).